PENGARUH INTENSITAS MENONTON KONTEN SKETSA KOMEDI DI TIKTOK DAN BRAND IMAGE TERHADAP KREDIBILITAS SUMBER PADA OWN MEDIA BANK MEGA - Reynard Aureliano; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This study analyzes the influence of comedy sketch viewing intensity and brand image on the credibility of Bank Mega's communication sources on TikTok. Using a quantitative approach, a survey was conducted among 353 TikTok users who had watched the bank's comedy content. Data were analyzed using multiple linear regression via SPSS. The results indicate that, both simultaneously and partially, viewing intensity and brand image have a positive and significant effect on source credibility. An Adjusted R Square value of 0.220 shows that these variables account for 22% of the variance in source credibility. These findings suggest that light entertainment content is an effective strategy for banking institutions to build trust and engagement with digital audiences, moving beyond traditional formal communication.